2016
DOI: 10.1186/s12877-016-0273-7
|View full text |Cite|
|
Sign up to set email alerts
|

Understanding the role of contrasting urban contexts in healthy aging: an international cohort study using wearable sensor devices (the CURHA study protocol)

Abstract: BackgroundGiven the challenges of aging populations, calls have been issued for more sustainable urban re-development and implementation of local solutions to address global environmental and healthy aging issues. However, few studies have considered older adults’ daily mobility to better understand how local built and social environments may contribute to healthy aging. Meanwhile, wearable sensors and interactive map-based applications offer novel means for gathering information on people’s mobility, levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 80 publications
(57 reference statements)
0
44
0
3
Order By: Relevance
“…The CURHA (Contrasted Urban settings for Healthy Aging) project addresses these challenges by combining data from wearable sensors and interactive map-based applications together with classical questionnaires on well-being, physical activity, perceived environments, and qualitative assessment of experience of places. Data from three cohorts located in Montreal, Paris, and Luxembourg shall generate evidence about which characteristics of urban environments are associated with active mobility, social participation, and well-being [27]. One approach for healthier urban aging was suggested by Green et al (2014) by investigating the impact of free bus travel on mobility and well-being of older citizens in London.…”
Section: Green Et Al 2014 [40] London Ukmentioning
confidence: 99%
“…The CURHA (Contrasted Urban settings for Healthy Aging) project addresses these challenges by combining data from wearable sensors and interactive map-based applications together with classical questionnaires on well-being, physical activity, perceived environments, and qualitative assessment of experience of places. Data from three cohorts located in Montreal, Paris, and Luxembourg shall generate evidence about which characteristics of urban environments are associated with active mobility, social participation, and well-being [27]. One approach for healthier urban aging was suggested by Green et al (2014) by investigating the impact of free bus travel on mobility and well-being of older citizens in London.…”
Section: Green Et Al 2014 [40] London Ukmentioning
confidence: 99%
“…Espaços ativos e bem iluminados não são propícios ao crime e aumentam a sensação de segurança de seus usuários e a facilidade de caminhar à noite 52,59,60 Sim Paradas de transporte público Maior densidade de paradas e estações de ônibus e metrô afeta positivamente a capacidade de locomoção porque o transporte público mais elevado sugere uma infraestrutura urbana bem desenvolvida 9,52,61 Não Presença de calçadas A presença de calçadas pode influenciar a prática de atividade física, principalmente a caminhada, já que facilita os deslocamentos por oferecer segurança e atratividade 54,55,62 Sim Qualidade das calçadas Uma infraestrutura de calçadas de boa qualidade suporta a caminhada como uma opção de modo viável e estimula a atividade física saudável. Degraus na calçada, piso escorregadio e má conservação estão entre as principais causas de acidentes de pedestres 63,64 Não Segurança viária A infraestrutura necessária para aumentar a segurança de pedestres e bicicletas na presença de tráfego como espaço/infraestrutura (por exemplo, calçadas, ciclovias), baixo volume de tráfego, faixas de pedestres, incentivam a caminhada 65,66 Não Uso misto do solo O nível de integração dentro de uma determinada área de diferentes tipos de usos para o espaço físico, incluindo residencial, escritório, varejo/comercial e espaço público. As pessoas que vivem perto de múltiplas e diversificadas oportunidades de varejo tendem a fazer viagens de compras mais frequentes, mais especializadas e mais curtas, muitas a pé 58,67,68 Não…”
Section: Conectividade Das Ruasunclassified
“…One way to realize these benefits is to ensure that urban public spaces and facilities are suitable for the elderly [2][3][4][5]. Providing safe, inclusive, and accessible public spaces can help the elderly obtain a higher quality of life and better health conditions [6,7]; thus, the sustainable development of cities can be more easily achieved [8].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Zhai [20] found that, as long as the destination is attractive, 23.4% of elderly people would visit high-quality parks that are far away from home. All of these studies also indicate that the elderly have stricter requirements and needs in terms of usability [19], accessibility [19], safety [16], comfort [15], and entertainment [20] in parks than younger people.On the whole, much research has been conducted on how urban planners should design suitable parks for the diversified needs of the elderly based on their health conditions [13][14][15], behavioral abilities, and characteristics [7,[13][14][15][16]. However, there is still no research on the spatial difference of the elderly suitability of parks in a single city or in certain kinds of cities.…”
mentioning
confidence: 99%
See 1 more Smart Citation